Prevalence and Incidence Rate of Diabetes, Pre-diabetes, Uncontrolled Diabetes, and Their Predictors in the Adult Population in Southeastern Iran: Findings From KERCADR Study - Najafipour, Hamid; Farjami, Maryam; Sanjari, Mojgan; Amirzadeh, Raheleh; Shadkam Farokhi, Mitra; Mirzazadeh, Ali (Frontiers in Public Health, 2021)
Abstract Background: Diabetes mellitus is among the most serious health challenges worldwide. We assessed the prevalence of pre-diabetes (pre-DM) and diabetes (DM), the effectiveness of diabetes management, the five-year incidence rate, and associated variables in the adult population in southeastern Iran. Methods: In a random cluster household survey (2014–2018), 9959 adult individuals aged 15–80 years were assessed for coronary artery disease risk factors, including diabetes mellitus in Kerman (KERCADRS, phase 2). Among these people, 2820 persons had also participated in phase 1 of the study five years earlier (2009-2011). Univariable and multivariable survey logistic regression models were used to identify the potential predictors of diabetes and pre-diabetes. Results: The prevalence of pre-DM was 12% (males 13.2% vs. females 11.1%), steadily increasing from 7.1% in the 15–24 years group to 18.4% in the 55–64 years group. The prevalence of DM was 10.2% (male and female, 7.9% and 10.8%, respectively), of which 1.9% were undiagnosed. DM was diagnosed in 10.6% of educated and 15.1% of illiterate people. The prevalence of diagnosed DM was lower in smokers (5.2% vs 8.7%) and dependent opium users (5.4% vs. 8.8 %). The prevalence of uncontrolled DM (HbA1c > 7 %) was 48.8%, increasing with age. The frequency of uncontrolled DM among people without and with treatment was 32% and 55.9%, respectively. Illiterate people had worse uncontrolled DM (55.6% vs. 39.6%). The 5-year incidence rate (persons/100person-years) was 1.5 for pre-DM and 1.2 for DM, respectively. The lowest and the highest incidence rate of DM belonged to the 15–34 years old group (0.5) and dependent opium users (2.4). The incidence rate was found to have a direct relationship with BMI and a reverse relationship with physical activity. Conclusion: pre-DM and DM affected 22.2% of the population. One-third of patients with diabetes had undiagnosed DM, and in 55.9% of people with diagnosed DM, treatment had been ineffective. Appropriate health interventions are needed to reduce the prevalence and health consequences of diabetes in the region.